Antibacterial and Antifungal Activity of Propyl-Propane-Thiosulfinate and Propyl-Propane-Thiosulfonate, Two Organosulfur Compounds from Allium cepa: In Vitro Antimicrobial Effect via the Gas Phase - Antonio Sorlozano-Puerto; Maria Albertuz-Crespo; Isaac Lopez-Machado; Lidia Gil-Martinez; Juan Jose Ariza-Romero; Alba Maroto-Tello; Alberto Baños-Arjona; Jose Gutierrez-Fernandez (MDPI AG, 2020)
Propyl-propane thiosulfinate (PTS) and propyl-propane thiosulfonate (PTSO) are two volatile compounds derived from Allium cepa with a widely documented antimicrobial activity. The aim of this study was to evaluate their anti-candidiasis activity and the ability of its gaseous phase to inhibit bacterial and yeast growth in vitro. The minimum inhibitory concentration of various antifungal products (including PTS and PTSO) was determined versus 203 clinical isolates of Candida spp. through broth microdilution assay. Additionally, the antimicrobial activity through aerial diffusion of PTS and PTSO was evaluated over the growth of a collection of bacteria and yeasts cultivated in agar plates. All yeasts were susceptible to the antifungals tested, except C. glabrata and C. krusei, that showed azole resistance. PTSO (MIC50 and MIC90 ranged from 4 to 16 mg/L and 8 to 32 mg/L, respectively) was significantly more active against yeasts than PTS (MIC50 and MIC90 ranged from 16 to 64 mg/L and 32 to 64 mg/L). Values were higher than those obtained for antifungal drugs. Gaseous phases of PTS and PTSO generated growth inhibition zones whose diameters were directly related to the substances concentration and inversely related to the microbial inoculum. The quantification of PTS and PTSO levels reached in the growth media through aerial diffusion displayed a concentration gradient from the central zone to the periphery. Only P. aeruginosa ATCC 27853 showed resistance, while yeasts (C. albicans ATCC 200955 and C. krusei ATCC 6258) presented the higher susceptibility to both compounds. These results suggest that PTS and PTSO display antibacterial and anti-candidiasis activity in vitro through aerial diffusion, having potential use in human therapy.